การประยุกต์ใช้แผนที่ผลลัพธ์ในการประเมินผลการดำเนินงานของเครือข่ายสร้างเสริมสุขภาพและครอบครัวตำบลโคกม่วง อำเภอเขาชัยสน จังหวัดพัทลุง - มณีน้อย, วิภาดา; สถิรปัญญา, จุฑารัตน์; สุธีรวุฒิ, พงค์เทพ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 26 No 2 (2558): Academic Services Journal, Prince of Songkla University, 2015)
การวิจัยเชิงพรรณนานี้มีวัตถุประสงค์เพื่อศึกษาแนวทางการประยุกต์แผนที่ผลลัพธ์ในการประเมินผลการดำเนินงานของเครือข่ายสร้างเสริมสุขภาพ กลุ่มผู้ให้ข้อมูล จำนวน 30 คน ประกอบด้วย กลุ่มภาคีหลัก กลุ่มภาคียุทธศาสตร์ และกลุ่มผู้เชี่ยวชาญ ผลการวิจัยพบว่า การประยุกต์ใช้แผนที่ผลลัพธ์มีประโยชน์ คือ 1) สามารถใช้ในกระบวนการวางแผน การดำเนินการ และการติดตามประเมินผล 2) ทำให้เกิดกระบวนการเรียนรู้ระหว่างภาคีหุ้นส่วน และนำไปสู่การพัฒนาในทุกขั้นตอนของแผนที่ผลลัพธ์ 3) การประยุกต์ใช้เหมาะสมกับการวางแผน และการค้นหาศักยภาพของภาคีหุ้นส่วน สำหรับปัญหาอุปสรรคในการนำไปใช้ คือ 1) ความจำเพาะของศัพท์เฉพาะทาง ทำให้กลุ่มผู้ใช้ขาดความเข้าใจและใช้เวลานานในแต่ละขั้นตอน 2) การประยุกต์ใช้จะได้ผลน้อยลงหากเจ้าหน้าที่ผู้รับผิดชอบมีการโยกย้าย เพราะการดำเนินงานจะขาดความต่อเนื่อง 3) ควรประเมินความพร้อมในการมีส่วนร่วมของภาคีหุ้นส่วนก่อนนำแผนที่ผลลัพธ์ไปใช้ 4) การดำเนินการในแต่ละขั้นตอน ควรใช้ผู้มีประสบการณ์ตรงเป็นผู้นำประเด็น และสื่อสารให้ผู้ร่วมเวทีเข้าใจได้ง่าย และ 5) แบบบันทึกมีจำนวนมาก ไม่เหมาะกับกลุ่มภาคีหุ้นส่วนที่เป็นคนในชุมชนซึ่งไม่มีความถนัดในการบันทึก ดังในการศึกษานี้ หากจะนำไปใช้ควรมีการเตรียมเจ้าหน้าที่ช่วยบันทึกหรือปรับแบบบันทึกให้สั้นและเข้าใจง่าย การศึกษานี้แสดงให้เห็นว่า หากเครือข่ายฯ นำแผนที่ผลลัพธ์ไปประยุกต์ใช้วางแผนดำเนินงาน มีความเหมาะสมในภาพรวม กลุ่มที่สามารถนำไปใช้ประโยชน์ ในการวางแผนเชิงนโยบาย และการประเมินผล คือ ภาคีหลักและภาคียุทธศาสตร์ ประโยชน์ที่เกิดขึ้น คือ สามารถนำมาใช้เป็นกรณีศึกษาให้กับท้องถิ่นอื่นๆ ได้ แต่ควรพิจารณาถึงระดับความรู้ของเครือข่ายฯ และขอบเขตให้มีความสอดคล้องกับสภาพและบริบทของพื้นที่ คำสำคัญ: แผนที่ผลลัพธ์, การประเมินผล, เครือข่ายสร้างเสริมสุขภาพและครอบครัว   The descriptive study of the outcome mapping application for evaluating the overall results of the health promotion’s network and family in Khok Moung Sub-district. Khao Chaison District, Phatthalung Province. The objective of this research was to study the approach of outcome mapping application for evaluating the network’s operation. The key informants consisted of Major Associate Group, Strategic Associate Group and Expert Group, a total of 30 persons. The results of this study found that conclusion of the benefits of outcome mapping for applying consisted of 1) the outcome journal can be used for planning, performing, monitoring and evaluating process 2) the initiative of learning process towards the outcome mapping development and 3) the application of outcome mapping, in particular, for planning and searching for a proficiency of the partnership associates. The problems of the outcome mapping application consisted of 1) a technical terms made a lack of sample’s understanding and spent long times in each procedures 2) the transference of the officials made a less of effective in applying the outcome mapping because of a discontinuity of the operation 3) should be evaluating the readiness of participation of the partnership associates before using the outcome mapping for implementation 4) in each procedures, it should be inviting the experts to participate for specifying the issues clearly and making an easy of understanding communication to the participants 5) the outcome journal was abundant and not suitable for the partnership associates group, which were the community’s people and do not have a skills of recording, likewise of this study. It should be prepared for the recording such as the officials providing or adjusting the outcome journal to be short, compact and easy of understanding. The study showed that if the network will use the outcome mapping to apply for planning, overall, it would be proper by adjusting in accordance with the context of the area. The persons who will use the research results for applying in working both in policy planning and evaluating, were the major associates and strategic associates. The outcome journal application can be used for the case study in the other local areas but it should be considered about the level of network’s knowledge and scope to be consistent with the context of each levels or areas. Keywords: outcome mapping, evaluation, network health promotion and families